FL Studio cookbook : over 40 recipes to help you master the art of music production with FL Studio - Friedman, Shaun (Quick answers to common problems., 2014)
"This book is built on recipes written in an easy-to-follow manner accompanied by diagrams and crucial insights and knowledge on what they mean in the real world. This book is ideal for musicians and producers who want to take their music creation skills to the next level, learn tips and tricks, and understand the key elements and nuances in building inspirational music. It's good to have some knowledge about music production, but if you have creativity and a good pair of ears, you are already ahead of the curve and well on your way."